PH-responsive silk fibroin-based CuO/Ag micro/nano coating endows polyetheretherketone with synergistic antibacterial ability, osteogenesis, and angiogenesis. (1st October 2020) - Yan, Jianglong; Xia, Dandan; Zhou, Wenhao; Li, Yangyang; Xiong, Pan; Li, Qiyao; Wang, Pei; Li, Ming; Zheng, Yufeng; Cheng, Yan
Abstract: Polyetheretherketone has been widely used for bone defect repair, whereas failures may happen due to implant loosening and infection. Thus, PEEK implant with multi-function (osteogenesis, angiogenesis, and bacteria-killing) is essential to solve this problem. Herein, copper oxide microspheres (µCuO) decorated with silver nanoparticles (nAg) were constructed on porous PEEK surface via silk fibroin. In vitro studies highlighted the pH controlled release ability of this coating. It liberated a high dose of Cu 2+ and Ag + at low pH environment (pH 5.0), leading to 99.99% killing of planktonic bacteria and complete eradication of sessile bacteria, avoiding biofilm formation. Under physiological environment (pH 7.4), a lower amount of leaked metal ions induced promoted ALP production, collagen secretion, and calcium deposition, as well as NO production, which indicated potentiated osteogenesis and angiogenesis. In vivo results displayed the highest new bone volume around, and the appearance of new bone inside porous structure of, PEEK implant with this coating in rabbit tibia, signified the abilities of this coating to promote bone regeneration and osseointegration. Our study established solid support for implants with this coating to be a successful bone defect repair solution. Statement of Significance: In this study, CuO/Ag micro/nano particles were incorporated into the porous surface of PEEK through polydopamine and silk fibroin layers. The design of this coating conferred pH-controlled release behavior to Cu 2+ and Ag + . High dose of metal ions were released at pH 5.0, which presented synergistic antibacterial ability and killed 99.99% of planktonic bacteria. Low concentration of metal ions were controlled by this coating at physiological environment, which potentiated osteodifferentiation of Ad-MSC in vitro and led to complete integration of implant with bone tissue in vivo . Graphical abstract: Image, graphical abstract